2000
DOI: 10.1073/pnas.97.8.4106
|View full text |Cite
|
Sign up to set email alerts
|

Ecological character displacement inPlethodon: Biomechanical differences found from a geometric morphometric study

Abstract: Ecological character displacement describes a pattern where morphological differences between sympatric species are enhanced through interspecific competition. Although widely considered a pervasive force in evolutionary ecology, few clear-cut examples have been documented. Here we report a case of ecological character displacement between two salamander species, Plethodon cinereus and Plethodon hoffmani. Morphology was quantified by using linear measurements and landmark-based geometric morphometric methods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
281
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(291 citation statements)
references
References 34 publications
6
281
1
3
Order By: Relevance
“…To discern if the level of phenotypic change of one population is greater than another, the test statistic jD E1 À D E2 j is calculated (e.g., Adams and Rohlf 2000). To discern if two populations differ in the direction of their phenotypic change vectors, their vector correlation is calculated as the inner product of the two vectors scaled to unit length: Cheverud and Leamy 1985, Schluter 1996, Klingenberg and Leamy 2001, Be´gin and Roff 2003.…”
Section: Multivariate Vectors Of Phenotypic Changementioning
confidence: 99%
“…To discern if the level of phenotypic change of one population is greater than another, the test statistic jD E1 À D E2 j is calculated (e.g., Adams and Rohlf 2000). To discern if two populations differ in the direction of their phenotypic change vectors, their vector correlation is calculated as the inner product of the two vectors scaled to unit length: Cheverud and Leamy 1985, Schluter 1996, Klingenberg and Leamy 2001, Be´gin and Roff 2003.…”
Section: Multivariate Vectors Of Phenotypic Changementioning
confidence: 99%
“…Numerous studies have demonstrated evidence consistent with morphological divergence as a result of interspecific competition (e.g., Fjeldså 1983;Dayan and Simberloff 1994;Chiba 1999;Adams and Rohlf 2000). For example, Adams and Rohlf (2000) reported a case of character displacement between two salamander species. Sympatric Plethodon hoffmani populations have evolved a faster closing, albeit weaker, jaw than allopatric populations, whereas sympatric P. cinereus populations have evolved a slower, stronger jaw.…”
mentioning
confidence: 99%
“…This pattern is most frequently attributed to ecological character displacement, evolutionary shifts of morphological traits in response to interspecific competition for resources between similar species (Brown and Wilson 1956;Grant 1972;Schluter 2000b). Numerous studies have demonstrated evidence consistent with morphological divergence as a result of interspecific competition (e.g., Fjeldså 1983;Dayan and Simberloff 1994;Chiba 1999;Adams and Rohlf 2000). For example, Adams and Rohlf (2000) reported a case of character displacement between two salamander species.…”
mentioning
confidence: 99%
“…In lizard studies, total size is usually represented by snout-vent length (SVL) (Hews, 1996;Butler and Losos, 2002;Kratochvil et al, 2003), and shape variation is analyzed via statistical size correction of the rest of the body-parts. However, in recent years the development of geometric morphometrics has allowed the direct study of shape variation (Bookstein, 1984;Rohlf, 1990;Rohlf and Slice, 1990;Corti, 1993;Adams and Rohlf, 2000;Adams et al, 2004). Although the application of geometric morphometrics in SD studies still needs to be explored, some authors report interesting SD patterns revealed by the application of such techniques in various animal taxa (Hood, 2000;Rosas and Bastir, 2002;Loy et al, 2004;Rufino et al, 2004;Valenzuela et al, 2004;Bruner et al, 2005).…”
mentioning
confidence: 99%